1994
DOI: 10.1159/000222967
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Glucose-Insulin-Potassium Infusion in Elective Coronary Surgery: Minor Benefit in Connection with Blood Cardioplegia?

Abstract: Objective: The goal of this study was to examine the metabolic and hemodynamic effects of a glucose-insulin-potassium infusion in elective coronary surgery, when blood cardioplegia was used for cardiac protection. Design and Patients: A prospective, randomized, open, clinical comparison was performed between 2 perioperative infusion regimens in 40 elective nondiabetic coronary artery bypass graft (CABG) surgery patients. Setting and Interventions: 20 patients (glucose-insulin-potassium – GIK – group) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the present study no difference was seen regarding CK-MB changes, which indi cates no essential additional protection by the amino acidenriched GIK infusion during the cross-clamp period. GIK infusion may be accompanied by great fluctuations in the blood glucose level, as seen in previous studies [6,8,23], How ever, no hypoglycemic episodes were seen in the present study, and hyperglycemia was well controlled in the A patients given additional insulin during CPB. Glutamate infusion is regarded as safe, although high plasma glutamate levels may induce a triad of unpleasent sensations, the Chinese restaurant syndrome with facial pressure, chest pain, and a burning sensation of the head and neck [25], The great elevations in plasma aspartate and glutamate levels dur ing the rewarming phase were mainly attributed to the blood cardioplegia component and to a minor degree to the amino acid-enriched GIK solution, as there was no statistical differ ence between the study groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study no difference was seen regarding CK-MB changes, which indi cates no essential additional protection by the amino acidenriched GIK infusion during the cross-clamp period. GIK infusion may be accompanied by great fluctuations in the blood glucose level, as seen in previous studies [6,8,23], How ever, no hypoglycemic episodes were seen in the present study, and hyperglycemia was well controlled in the A patients given additional insulin during CPB. Glutamate infusion is regarded as safe, although high plasma glutamate levels may induce a triad of unpleasent sensations, the Chinese restaurant syndrome with facial pressure, chest pain, and a burning sensation of the head and neck [25], The great elevations in plasma aspartate and glutamate levels dur ing the rewarming phase were mainly attributed to the blood cardioplegia component and to a minor degree to the amino acid-enriched GIK solution, as there was no statistical differ ence between the study groups.…”
Section: Discussionsupporting
confidence: 83%
“…Most GIK studies have been done using crystalloid cardiople gia techniques. Effective myocardial protection by means of modern blood cardioplegic techniques may diminish the need for additional intravenous metabolic support [23], However, there may be myocardial areas at risk due to improper or un even distribution of the blood cardioplegia solution, e. g. due to occlusion of coronary artery branches (antegrade techni que) or for technical reasons, such as malposition of the sinus cannula (retrograde technique) [24]. In the present study no difference was seen regarding CK-MB changes, which indi cates no essential additional protection by the amino acidenriched GIK infusion during the cross-clamp period.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five of the 38 studies report positive results with regard to GIK infusions [12,[16][17][18]21,26,[32][33][34][37][38][39]46,49,51,[53][54][55][56][57]59,[63][64][65][66][67], 11 studies report neutral or negative results [13,22,27,35,52,58,60,61,[68][69][70], and two studies [50,62] argue neither for nor against GIK infusions, as both studies were primarily not aimed at GIK effects but on other endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative AF data were reported in 10 studies (1540 patients) ( Table 2) (15)(16)(17)(18)(24)(25)(26)29,33,34), and AF was the primary end point in two studies (19,27). Details of AF outcome assessment are included in Table 3.…”
Section: Postoperative Afmentioning
confidence: 99%
“…However, the data could not be pooled because some studies reported mean glucose levels and other studies reported the frequency of clinically significant or protocol-defined glycemic abnormalities. Of the studies that reported glycemic abnormalities, six reported frequencies of hypoglycemia requiring treatment (18)(19)(20)(21)26,34), and in five of these studies, hypoglycemia was more frequent among the GIK/GI-treated patients (18)(19)(20)(21)34). Twelve studies reported data on hyperglycemia or mean glucose levels.…”
Section: Gik/gi-related Adverse Eventsmentioning
confidence: 99%